2019
DOI: 10.7150/thno.33282
|View full text |Cite
|
Sign up to set email alerts
|

KLF5 downregulation desensitizes castration-resistant prostate cancer cells to docetaxel by increasing BECN1 expression and inducing cell autophagy

Abstract: KLF5 is frequently deleted or downregulated in prostate cancer. However, it is not known whether downregulation of KLF5 is associated with the response of prostate cancer cells to chemotherapy and/or prognosis of patients.Methods: We monitored cell growth by MTT and colony formation assays, and cell autophagy through tandem fluorescence microscopy and transmission electron microscopy. Gene expression was analyzed by RT-qPCR and Western blotting. We determined the binding of KLF5 together with HDAC3 on the becl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 37 publications
4
38
2
Order By: Relevance
“…Autophagy has been reported to decrease the sensitivity of hepatoma cells to chemotherapeutic agents by affecting their apoptotic potential [23]. Evidence has also suggested that autophagy plays critical roles in docetaxel chemoresistance [5]. In present study, we performed studies in PC3 and DU145 cells con rmed that MSCs could signi cantly induce autophagy in CRPC cells (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Autophagy has been reported to decrease the sensitivity of hepatoma cells to chemotherapeutic agents by affecting their apoptotic potential [23]. Evidence has also suggested that autophagy plays critical roles in docetaxel chemoresistance [5]. In present study, we performed studies in PC3 and DU145 cells con rmed that MSCs could signi cantly induce autophagy in CRPC cells (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…The procedure was described previously 8 . The following antibodies were used: KLF5 (ab24331), MMP9 (ab38898), and IGF1 (ab9572) (Abcam, Cambridge, UK), p-STAT3 (Tyr705) (#9145), STAT3 (#9139), HDAC1 (#5356), and AR (#5153) (Cell Signaling Technology, Beverly, MA, USA), MMP2 (10373-2-AP) (Proteintech, Rosemont, IL, USA), and β-actin (ComWin Biotech Co. Beijing, China).…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…Krüpple-like transcription factor 5 (KLF5/IKLF/ BTEB2), which is a zinc-finger transcription factor, has various functions in different cellular processes, including proliferation, apoptosis, invasion, and differentiation 4,5 . KLF5 binds specifically to the CA-box and GC-rich regions on target promoters and can recruit other transcription factors and epigenetic enzymes, such as ERβ, SMAD4, p300, and HDAC3, into the transcriptional complex to activate or repress the target gene transcription [6][7][8] . Frequent deletion of the KLF5 gene was reported in human PCa 9 , and protein degradation and promoter DNA methylation also led to KLF5 downregulation in PCa 10 .…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the underlying mechanism of BDH2-induced apoptosis and autophagy, we examined the effect of BDH2 on the expression of classic autophagy-related pathways such as AMPK, MAPK/ Erk1/2, and PI3K/Akt/mTOR signalling [21,22]. As shown in Fig.…”
Section: Ros/pi3k/akt/mtor Axis Contributes To Bdh2-induced Apoptosismentioning
confidence: 99%